Co-Branding Serum Azarine X Marvel Terhadap Purchase Intention (Institut Agama Islam Negeri Kudus, 2023)
The study aims to empirically examine the influence of corporate co-branding on brand equity, brand extension, and brand preference towards purchase intention for Azarine X Marvel serum products. This research employed a quantitative approach of explanatory research type, involving 120 sample respondents who are students of FEBI IAIN Kudus from the 2019-2020 academic year. The results of hypothesis testing using t-test with criteria of t-table > 1.1980 and significance value < 0.05 indicate that the variables of brand equity, brand extension, and brand preference in corporate co-branding have a significant influence on purchase intention, with obtained t-values of 10.898, 5.950, and 2.047, and significance levels of 0.000, 0.000, and 0.04, respectively. The R2 test reveals that the influence of brand equity, brand extension, and brand preference on purchase intention through corporate co-branding is 62.9%, with the remaining 37.1% influenced by unmeasured variables in this research.